The Story of Abraham and Lot Based on Genesis 13:1-17 and Its Implications for Problem Solving in Today's Christian Family - Kawa, Simson Mau; Ledoh, Novita Krydayanti; Tofeto, Vantri; Snae, Vindry Omanda; Nubatonis, Miady; Banu, Maher (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The story of Abraham and Lot in Genesis 13:1-17 describes the conflict over land ownership they faced after returning from Egypt, which has important implications for how Christian families today resolve problems, especially in terms of spiritual priorities and decision-making. The story of Abraham and Lot also shows the importance of open communication and compromise in resolving conflicts and making wise decisions based on the values of the kingdom of God in building a harmonious family. The aim is to reveal how the story of Abraham and Lot can be a guide for Christian families today, in building harmonious relationships. The research method used is Biblical, namely to analyze the story of Abraham and Lot in Genesis 13:1-17. This approach focuses on interpreting the biblical text holistically, and connecting it with the context of today's family and collecting existing data.